Advances in mesenchymal stromal cell therapy for acute lung injury/acute respiratory distress syndrome - Liu, Chang; Xiao, Kun; Xie, Lixin (Frontiers in Cell and Developmental Biology, 2022)
Acute lung injury (ALI)/acute respiratory distress syndrome (ARDS) develops rapidly and has high mortality. ALI/ARDS is mainly manifested as acute or progressive hypoxic respiratory failure. At present, there is no effective clinical intervention for the treatment of ALI/ARDS. Mesenchymal stem cells (MSCs) show promise for ALI/ARDS treatment due to their biological characteristics, easy cultivation, low immunogenicity, and abundant sources. The therapeutic mechanisms of MSCs in diseases are related to their homing capability, multidirectional differentiation, anti-inflammatory effect, paracrine signaling, macrophage polarization, the polarization of the MSCs themselves, and MSCs-derived exosomes. In this review, we discuss the pathogenesis of ALI/ARDS along with the biological characteristics and mechanisms of MSCs in the treatment of ALI/ARDS.